Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11356-015-5081-7
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption studies on copper (II) and cadmium (II) using pretreated rice straw and rice husk

Abstract: This study investigated the adsorption and removal behaviour of copper (Cu) (II) and cadmium (Cd) (II) ions using rice husk and rice straw in aqueous solutions. Different parameters were used to investigate their adsorption performance in saline conditions and the optimal level of biosorption at different pH levels. The main parameters were pH (3, 6 and 9), initial concentration level of heavy metals (Cu (II) 5, 10, 20, 40 and 60 mg/L and Cd (II) 0.5, 1, 2, 4 and 8 mg/L, respectively), salinity (0, 50 and 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 73 publications
2
22
0
Order By: Relevance
“…However, the plotting of 1/qe against 1/Ce values presented in Figure 5(b) for the Langmuir model offered an R 2 of 0.7148. The correlation coefficient (R 2 ) indicated the compliance of the isotherm models with the experimental data (Li et al, 2017). Hence, these indicated that the Langmuir isotherm model was less adequate in describing the relationship between adsorption capacity and their equilibrium concentration.…”
Section: Adsorption Isothermmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the plotting of 1/qe against 1/Ce values presented in Figure 5(b) for the Langmuir model offered an R 2 of 0.7148. The correlation coefficient (R 2 ) indicated the compliance of the isotherm models with the experimental data (Li et al, 2017). Hence, these indicated that the Langmuir isotherm model was less adequate in describing the relationship between adsorption capacity and their equilibrium concentration.…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…Then RS was washed and neutralized to around pH 7 using HCl solution. Cleaned RS was dried in an oven at 80 o C for 24 h before use (Li et al, 2017;Nam et al, 2018). Purified RS was meshed to set a homogeneous size of 2.5 mm.…”
Section: Rice Straw (Rs)mentioning
confidence: 99%
“…In addition to large amounts of SiO2, The rice straw consists mainly of lignin, hemicellulose, cellulose, extractives, mineral ash and water, ( Li et al 2017). The lignin can interact promptly with cations, idea exchanging with protons and chelating with the metal ion, ( Rocha et al 2009).…”
Section: (A) (B) (C) Figure 4 Sem Images Of the Rice Straw (Rs) At Tmentioning
confidence: 99%
“…It is important to note that arsenic (As) is a metalloid and selenium (Se) is a nonmetal, however, the term "heavy metal" will be used for the description of the elements studied in this paper. Although trace concentration of some of these elements (Fe, Cu, Cr, Zn, Se, Mn, Ni) are vital for some biochemical processes and physiological functions, they can persist in the environment and can cause serious health problems even at low concentrations (Ali et al, 2016;Amuda et al, 2007;Aremu et al, 2002;Chowdhury et al, 2016;Gautam et al, 2014;Karadag, 2008;Koubaissy et al, 2014;Li et al, 2017;Sencan et al, 2015;Wan Ngah and Hanafiah, 2008;Wang and Chen, 2006).…”
Section: Introductionmentioning
confidence: 99%